Being a teacher with disabilities: Experiences from across five countries - and Jun 10, Nidhi Singal |; Education, 2024 | (Disabilities, 2024)
Debates on inclusive education tend to overlook the need for diversity in the education workforce, particularly in relation to employment of teachers with disabilities in mainstream schools.